Consumer Protection and the Incentive to Become Informed. - Armstrong, M; Vickers, J; Zhou, J (MIT Press, 2009)

(untitled)
We discuss the impact of consumer protection policies on consumers' incentives to become informed of the best deals available in the market. In a market with costly information acquisition, we find that imposing a cap on suppliers' prices reduces the incentive to become informed of market conditions, with the result that prices paid by consumers (both informed and uninformed) may rise. In a related model where consumers have the ability to refuse to receive marketing, we find that this ability softens price competition and can make all consumers worse off.